1988
DOI: 10.1037/h0084194
|View full text |Cite
|
Sign up to set email alerts
|

Location confusions in visual information processing.

Abstract: Dixon (1986) proposed a location-confusion model to account for an interference effect that occurs when subjects decide whether a briefly presented target item appeared in a briefly presented array. In the model, it was assumed that information about the location of items decays quickly and that subjects sometimes have difficulty deciding whether a particular identity code corresponded to the target or the array. The present report describes two additional experiments using this paradigm. Experiment 1 confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…On one hand, one may regard the result as an inherent part of the interference effect; that is, the interference effect consists of a tendency to make false alarms at short SOAs. This interpretation is supported by the robustness of this pattern of results: It was found in all five of the experiments reported by Dixon (1986), as well as in Dixon (1985), Dixon and Twilley (1988), and in some of the conditions of Briand and Klein (1988). On the other hand, one might regard the false alarm increase as a separate effect from the overall decrease in accuracy.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…On one hand, one may regard the result as an inherent part of the interference effect; that is, the interference effect consists of a tendency to make false alarms at short SOAs. This interpretation is supported by the robustness of this pattern of results: It was found in all five of the experiments reported by Dixon (1986), as well as in Dixon (1985), Dixon and Twilley (1988), and in some of the conditions of Briand and Klein (1988). On the other hand, one might regard the false alarm increase as a separate effect from the overall decrease in accuracy.…”
supporting
confidence: 60%
“…Recently, a number of researchers have reported an interference effect that occurs when subjects view a brief alphanumeric display followed by a single target item (Briand & Klein, 1988; Di Lollo & Moscovitch, 1983; Dixon, 1986; Dixon & Twilley, 1988). Generally, it is found that subjects' ability to decide whether the target item was present in the array is poor when the target follows the array by 100–200 ms, but improves with either longer or shorter stimulus-onset asynchronies (SOAs).…”
mentioning
confidence: 99%
“…The pseudoletters were constructed out of letter parts so that they would contain letter-like features but would not resemble any actual letter very strongly. The pseudoletters were modelled after those used by Dixon and Twilley (1988) and were also about 1.0° in height. The items were chosen randomly without replacement from the set of 26 letters or 26 pseudoletters.…”
Section: Methodsmentioning
confidence: 99%
“…Without representations, developed during an initial familiarizing or label-learning phase to provide top-down influence, the forms would have to be distinguished at the level of visual features (Dixon & Twilley, 1988). Lengthening the exposures as in Experiment 1 allows the subject more time to select and retain some feature or features that may be matched against those of items in the character set.…”
Section: Discussionmentioning
confidence: 99%
“…Separate processing of identity and location information during the transfer from the Feature Buffer to the Character Buffer allows scrambling that produces mislocations (Butler, 1981). Others have proposed that location information merely decays more quickly than identity information, leaving observers less sure of the relative positions of items than of their identities (Dixon, 1986; Dixon & Twilley, 1988). More recently, Driver and Baylis (1991) proposed that letter identities are derived in parallel rather than serially, although letter location information is not automatically produced when letter identity is determined.…”
mentioning
confidence: 99%